Pengaruh Kepatuhan dan Kesadaran Wajib Pajak Terhadap Kewajiban Membayar Pajak Orang Pribadi di Kecamatan Tasikmadu – Jawa Tengah - Maharani, Maharani; Endaryati, Eni; Kusumo, Haryo; Rokhman, Nur (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze the effect of taxpayer compliance and taxpayer awareness on the obligation to pay individual income taxes in Tasikmadu District. Taxes are the primary source of state revenue; therefore, compliance and awareness play a crucial role in optimizing tax collection. However, the compliance level of individual taxpayers in Tasikmadu District remains suboptimal, as many taxpayers have not fulfilled their obligations accurately and on time. This research employed a quantitative approach with a survey method. The population consisted of individual taxpayers registered in Tasikmadu District, and a total of 400 respondents were selected using Slovin’s formula. Data were collected through questionnaires with a Likert scale and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of statistical software. The results indicate that taxpayer compliance has a positive and significant effect on the obligation to pay taxes. Taxpayer awareness also shows a positive and significant effect. Simultaneously, compliance and awareness significantly influence individual tax obligations in Tasikmadu District. The adjusted R² value of 0.420 demonstrates that these two variables explain 42.0% of the variation in tax obligations, while the remaining 58.0% is influenced by other factors not examined in this study. Based on these findings, it is recommended that the Directorate General of Taxes improve tax education and socialization programs, as well as expand the use of technology-based tax services to strengthen taxpayer compliance and awareness. Strengthening these aspects is expected to enhance tax revenue optimization and support sustainable national development.